(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This research presents how the purchasing behavior of millennials in recent years has incorporated additional valuation elements to the traditional ones for decision-making, particularly in their orientation to the consumption of tourism goods and services. The main purpose of this research is to identify tourism marketing strategies aimed at millennials that include sustainable practices to generate a communicative link and anchor with the consumer. It is documentary research developed through the review of specialized literature, and through the analysis of scientific articles, marketing journals, consumer behavior, and tourism. In addition, an analysis of each document was carried out to gather conclusions that explain this phenomenon. The main findings of this research show an evident orientation of millennials to evaluate tourism companies based on their digital reputation, on the sustainable practices they use in their internal and external communication, on the comments that their peers (other millennials) express on social media, and tourist websites.